A research agenda on patient safety in primary care. Recommendations by the LINNEAUS collaboration on patient safety in primary care - Verstappen, Wim (Eur J Gen Pract, 2015)
Background: Healthcare can cause avoidable serious harm to patients. Primary care is not an exception, and the relative lack of research in this area lends urgency to a better understanding of patient safety, the future research agenda and the development of primary care oriented safety programmes. Objective: To outline a research agenda for patient safety improvement in primary care in Europe and beyond. Methods: The LINNEAUS collaboration partners analysed existing research on epidemiology and classification of errors, diagnostic and medication errors, safety culture, and learning for and improving patient safety. We discussed ideas for future research in several meetings, workshops and congresses with LINNEAUS collaboration partners, practising GPs, researchers in this field, and policy makers. Results: This paper summarizes and integrates the outcomes of the LINNEAUS collaboration on patient safety in primary care. It proposes a research agenda on improvement strategies for patient safety in primary care. In addition, it provides background information to help to connect research in this field with practicing GPs and other healthcare workers in primary care. Conclusion: Future research studies should target specific primary care domains, using prospective methods and innovative methods such as patient involvement.